Expression of influenza virus hemagglutinin activates transcription factor NF-kappa B. - Pahl, H L (1995)
Influenza virus infection initiates transcription of a variety of genes for cytokines such as tumor necrosis factor alpha (TNF-alpha), TNF-beta, interleukin 1 alpha, (IL-1 alpha), IL-1 beta, IL-2, IL-4, IL-6, IL-10, granulocyte macrophage colony-stimulating factor, and gamma interferon. However, the mechanism by which virus infection elicits cytokine expression remains unknown. Six influenza virus-induced cytokine genes are targets for the inducible transcription factor NF-kappa B, a central regulator of the human immune response. Here, we show that expression of a single influenza virus protein, the virion surface hemagglutinin, strongly activates NF-kappa B DNA binding and transactivation. Activation is inhibited in the presence of the antioxidant dithiothreitol, suggesting that, similar to the findings for previously described inducers of NF-kappa B, hemagglutinin expression generates radical oxygen intermediates which activate the transcription factor. Hemagglutinin is the first secretory and structural viral protein reported to activate NF-kappa B and thus represents a new class of inducers for this transcription factor. We discuss these results in the context of clinical complications of influenza virus infection.